Przez kwasową psychiatrię do kwasowego komunizmu. Renesans psychodeliczny w psychiatrii jako szansa na zmianę paradygmatu - Stupak, Radosław (Praktyka Teoretyczna, 2021)
Mark Fisher wrote „the task of repoliticizing mental illness is an urgent one if the left wants to challenge capitalist realism.” This paper attempts to develop this thought and show how the repoliticization of issues defined as mental illnesses that could have an emancipatory potential and undermine capitalist realism could look like and how it could be related to the contemporary phenomenon of „psychedelic renaissance”. This repoliticization could constitute the first step towards acid communism – a step that would enable a comprehensive formulation of the project, the imagining of both acid communism itself as well as the road towards it. Even though psychedelics could provide an impulse for the change of the dominant psychiatric paradigm and the reorganization of mental health services, the process of the interception of these substances by the alienating and commodificating orders of psychiatry and capitalism can already be observed, so that both of the intertwined and mutually supporting orders can in fact be strengthened. From this perspective the institution of psychiatry becomes a key element preserving the status quo, which makes the imagining of the end of capitalism impossible. Politicization of mental health, that could question capitalist realism, needs to be connected with the deconstruction of the ideology of psychiatry.